Effect of superhydrophobic coating on the mechanical properties and colourfastness of lawsonia inermis, azadirachta indica and curcuma longa dyed cotton fabrics - Thana Singam, Rupashinii (2021)
This research focuses on the utilization of natural dyes based on Lawsonia Inermis, Azadiractha Indica and Curcuma Longa coated with superhydrophobic coating on cotton fabric. Natural dyes were used in this research and superhydrophobic coating for self-cleaning of fabrics. The fine powder dye was divided into eight concentrations which were 0.25 g/ml (A), 0.50 g/ml (B), 0.75 g/ml (C), 1.00 g/ml(D), 1.25 g/ml (E), 1.50 g/ml (F), 1.75 g/ml (G) and 2.00 g/ml (H). The method that involved in this research was direct dyeing for Lawsonia Inermis, Azadirachta Indica and Curcuma Longa dye for cotton fabric. Dyed cotton fabrics were coated with superhydrophobic coating using spraying technique. The coated and uncoated dyed cotton fabric was tested physically and mechanically. The F (1.50 g/ml) of dye concentration of uncoated and coated fabrics of Lawsonia Inermis, Azadirachta Indica and Curcuma Longa shows the highest physical and mechanical strength. The coated dyed cotton fabric with the Lawsonia Inermis, Azadirachta Indica, Curcuma Longa indicated 5 (excellent) for crocking test. The bursting strength for Lawsonia Inermis was (17.07 kPa), Azadirachta Indica (17.09 kPa), Curcuma Longa (17.08 kPa). Then, the weight loss for abrasion test at 5,000 and 20,000 cycles for Lawsonia Inermis were (2.41%, 2.51%), Azadirachta Indica (2.43%, 2.53%), Curcuma Longa (2.46%, 2.56%). As a conclusion natural dyes based on Lawsonia Inermis, Azadirachta Indica and Curcuma Longa can be used as an alternatives dyes in textile industry.